Further education in psychedelic-assisted therapy – experiences from Switzerland - H.D. Aicher; F. Müller; P. Gasser (BMC Medical Education)
Abstract The growing interest in psychedelic-assisted therapy (PAT) for treating psychiatric disorders such as treatment-resistant depression, PTSD, and anxiety has led to an increasing demand for specialized training. In Switzerland, MDMA, psilocybin, and LSD are applied in the framework of limited medical use as exceptional treatment options since 2014. The Swiss Medical Association for Psychedelic Therapy (SÄPT) has been a key player in addressing the need for education, offering a comprehensive, three-year training program for physicians and psychologists. This curriculum integrates theoretical knowledge with hands-on experience, emphasizing the therapeutic relationship, ethical considerations, and the management of altered states of consciousness induced by psychedelics. This article gives an overview of the structure and framework of the training and addresses topics covered by the program through theoretical teaching and retreats focusing on practical learning. However, the demand for these programs far exceeds supply. This gap is expected to widen as psychedelics potentially become regulated prescription medications. In response, several organizations have expanded their educational offerings, including further education trainings, workshops, conferences, and symposia. Overall, there is a need for more comprehensive and accessible training programs to meet the growing demand. The evolving landscape of psychedelic research, regulatory changes, and diverse patient populations require flexible and adaptive training models. As the field progresses, it is essential to establish certification standards and ensure the continued quality of training programs to ensure the safe and effective use of PAT in clinical trials and practice.